A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China - Chen, Zhi-Teng; Hou, Jia-Lin (Zootaxa, 2020)
A new species of Hemacroneuria Enderlein, 1909, H. baotianmana sp. nov. is described and illustrated from Henan Province of central China and Shaanxi Province of northwestern China. Supplementary descriptions and new images are provided for Chinoperla mengmanensis Qian & Du, 2012 based on new material from Yunnan Province of southwestern China. The female of C. mengmanensis is described for the first time.